Development of Android-Based Learning Media to Improve Cognitive Ability of Grade XII Students at MAN 2 Bojonegoro on the Topic of Fiqih Sources of Islamic Law - M. Nizar Chariri; Yeri Sutopo; Samsudin Anis (Universitas Negeri Semarang, 2026)
This study aims to design Android-based learning media combined with a Computer Based Test (CBT), and to examine its level of feasibility, practicality, and effectiveness in raising student learning outcomes. The content focus is concentrated on the subject of Fiqih, particularly the various sources of Islamic law relating to inheritance studies (mawaris). The research method applied is Research and Development (R&D), adopting the ADDIE framework (Analysis, Design, Development, Implementation, Evaluation). The research subjects involved grade XII students of MAN 2 Bojonegoro as the experimental group and MA Al-Rosyid as the control group. Data were collected through expert validation sheets, teacher practicality response questionnaires, and cognitive learning outcome tests, then analyzed using feasibility tests, normality tests, homogeneity tests, N-Gain, and an independent sample t-test. The media was rated very feasible, based on an average score of 4.59 from media experts and 4.70 from content experts. The practical feasibility assessment carried out by ten Fiqih subject teachers across several MA schools in Bojonegoro Regency produced a cumulative score of 95.45%, placing it in the very practical category. Implementation of the media was shown to significantly improve the cognitive ability of students in the experimental class, reaching an average N-Gain index of 70.08%, categorized as fairly effective, which exceeded the control class result of only 50.63%. The results of the independent t-test further confirmed a significant difference in effectiveness between the experimental class that used this integrated learning media and the control class.